Design and Fabricate Filament Winding Machine and Analysis of Cotton/Epoxy and Pandanus/Epoxy - Mahdi Ahmad Saad, Elsadig (1997)
This project concerned with filament wound cotton/epoxy and pandanus/epoxy composite tubes. Monofilament winding machine has been designed and fabricated. It is later used in fabricating the composite tubes. The performance of this machine was measured. The results revealed that the winding angle depended primarily on the carriage speed traversing at speed synchronised with mandrel rotation. Also, the efficiency of the machine showed that winding at high angles relative to rotational axis was very high (i.e. at 90° the efficiency is 100%). Winding at low angles (parallel to rotational axis) was difficult. The surface finish depended on the fibre tension, the wiping process and band formation 0. e. smooth surface finish at 4.4 kN). The behaviour of filament wound cotton/epoxy and pandanus/epoxy composite tubes was studied experimentally. Circular cylindrical of cotton/epoxy and pandanus/epoxy were loaded in uni-axial compression. The test results show that cotton/epoxy hoop tubes the maximum strength was found to be 13kN and for the 80° cotton/epoxy tubes was found to be 10.6kN. For the pandanus/epoxy hoop tube the maximum strength was found to be 0.3kN. Flat specimens were also prepared from wound tubes and loaded in uni-axial tension. The cotton/epoxy composite tubes were tested under internal pressure. The results show that the maximum pressure that the tube can be withstand was found to be 5 bar. Maximum stress and maximum strain theories are used to predict the failure of these tubes. Finite element method also used in the analysis of cotton/epoxy composite tubes. The uni-axial tensile test results show that the mean modulus was found to be 3 867.6 MPa for the 80° laminated tensile test specimens and 1067.0 MPa for hoop (90°) laminated tensile test specimens. The maximum strain mean in 80° and 90° laminated tensile specimens are essentially the same (0.1). The urn-axial compression test results show that in the condition of hoop (90°) laminated tubes and 80° laminated tubes the load-displacement curve is linearly up to initial failure.